Bleeding and its Types, Organization of Emergency Assistance in Bleeding - Asatullayev, Anvar Narzullayevich; Jabborova, Oygul Gaparovna (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides and overview on bleeding and its types, the organization of emergency care in hemorrhage, and the volume and rate of bleeding will also depend on the size of the injured vessel, whether the wound is superficial or deep cut and crushed. Men are a little more intolerant of blood loss than women, which is related to menstruation in women. Hemorrhage in the elderly is more common, and comorbidities and infectious diseases that occur in them have been studied as changes in the weakening of the vascular walls as a result of blood bile poisoning.